Regulatory roles of the NMDA receptor GluN3A subunit in locomotion, pain perception and cognitive functions in adult mice. (5th November 2012) - Mohamad, Osama; Song, Mingke; Wei, Ling; Yu, Shan Ping
Key points Adult glutamate NMDA receptor subunit 3A (GluN3A) knockout (KO) mice showed slow locomotor activity, motor deficits and increased pain sensation. Hippocampal slices from juvenile and adult GluN3A KO mice showed greater long‐term potentiation compared with wild‐type slices. Adult GluN3A KO mice showed enhanced abilities in learning and memory tasks. GluN3A deletion resulted in increased expression and/or phosphorylation of Ca2+/calmodulin‐ dependent kinase II in the brain. This is the first investigation showing that deletion of GluN3A in the embryonic stage has imperative impacts on multiple behaviours in adults. Abstract Since the discovery of the glutamate NMDA receptor subunit 3A (GluN3A), the functional role of this unique inhibitory subunit has been largely obscure. GluN3A expression is high in the neonatal brain but declines to a low level in the adult brain; it is thus commonly believed that GluN3A does not have a major functional impact in adulthood. Using wild‐type (WT) and GluN3A knockout (KO) mice, we show here that deletion of GluN3A affected multiple behavioural functions in adult animals. GluN3A KO mice showed impaired locomotor activity on a variety of motor function tests, and increased sensitivity to acute and sub‐acute inflammatory pain. GluN3A KO mice also showed enhanced recognition and spatial learning and memory functions. Hippocampal slices from juvenile and adult GluN3A KO mice showed greater long‐term potentiation (LTP) compared with WT slices. GluN3A deletion resulted in increased expression of Ca2+/calmodulin‐dependent kinase II (CaMKII) in the forebrain, and the phosphorylated CaMKII level upon LTP induction was significantly higher in the GluN3A KO hippocampus compared with WT controls. CaMKII inhibition abrogated the enhanced LTP in GluN3A KO slices. These data reveal for the first time that the presence of GluN3A may have profound impacts on several functional/behavioural activities in adult animals, and could be a therapeutic target for neurological disorders associated with NMDA receptor functions.